Pericyte FAK negatively regulates Gas6/Axl signalling to suppress tumour angiogenesis and tumour growth - Tanguy Lechertier (Nature Portfolio, 2020)
Focal adhesion kinase (FAK) is required for tumour angiogenesis and growth. Here, the authors show that deletion of pericyte FAK upregulates Gas6-Axl mediated Cyr61 production, which increases endothelial cell proliferation and angiogenesis, while elevating tissue factor production to enhance tumour cell proliferation.